The Survey on Infinite Groups: a Guide to Some Classical Areas - Kurdachenko, L.A.; Pypka, A.A.; Semko, Mykola Mykolaiovych; Subbotin, I.Ya. (Institute o f Mathematics of NAS of Ukraine, 2016)
The book is a kind of guide that makes it possible to obtain information about the basic concepts and results of some important parts of infinite groups theory. The book can be useful for algebraists intending to take a closer look at the theory of infinite groups in order to use obtained results there. It will also be useful for students who aim to become acquainted with the subject.

Книга є своєрідним довідником, який дає можливість отримати інформацію про базові поняття та результати деяких важливих розділів теорії нескінченних груп. Книга може бути корисною для алгебраїстів, що мають намір ближче познайомитись з теорією нескінченних груп та використовувати отримані в ній результати. Вона буде також корисною для аспірантів та студентів, які ставлять за мету познайомитись з цією тематикою.
Огляд результатів теорії нескінченних груп: рекомендації щодо класичних розділів
Keywords: infinite group; normal subgroup; Dedekind group; metacyclic subgroup; metagamiltonian group; нескінченна група; free abelian group; нормальна підгрупа; дедекіндова група; метациклічна підгрупа; метагамільтонова група